Self-powered multifunctional sensing based on super-elastic fibers by soluble-core thermal drawing - Mengxiao Chen (Nature Portfolio, 2021)
Though thermal drawing methods are attractive for fabricating fiber-based sensor devices, existing methods allow limited access to low viscosity and low modulus materials. Here, the authors demonstrate a two-step soluble-core fiber fabrication method with wide applicability to soft polymer materials.